Beiträge zur Insektenfauna der DDR: Lepidoptera - Ethmiidae. - Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1973)
On the basis of a revision of all available collections, oft the author’s collection and of a critical evaluation of relevant publications, a faunistic treatment of the Ethmiidae of the GDR, subdivided for the districts, is presented. For the five species established in this area, a total of 347 finds are registered and evaluated from these sources. The material of about 70 per cent of the registered finds, 431 specimens, were vailable. The species E. candidella Alpheraki, whose presence in the south of the GDR may yet be discovered, is included in the discussion. A key to these Lepidoptera and a summary of our present knowledge of the caterpillars and pupae of the species under consideration are given.